LITERATURE CIRCLE IN PROMOTING YOUNG LEARNERS’ READING COMPREHENSION - Fitriana Fitriana (HOLISTICS, 2020)
Reading English literary text for Indonesian students is not an easy task since reading text for literary experience is different from reading for information. This explains why reading across the curriculum or reading in the content has become a critical component of many school improvement efforts. Helping students learn from textbooks is more complicated than asking them to read the text and answer question. Teachers not only should convince them to develop effective strategies in order to read different texts, but also to develop their thoughtful interpretations of what they read and how they approach the task in order to be active paticipants in the classroom. Literature circles which offer the potential to promote reading for enjoyment by harnessing the social networks that exist within the peer group provide a way for students to promote their reading comprehension as they read, discuss, and respond to books.